2012
DOI: 10.1002/14651858.cd004350.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Regional versus general anaesthesia for caesarean section

Abstract: There is no evidence from this review to show that RA is superior to GA in terms of major maternal or neonatal outcomes. Further research to evaluate neonatal morbidity and maternal outcomes, such as satisfaction with technique, will be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 47 publications
8
90
1
5
Order By: Relevance
“…However, we did not include this factor in our prediction model, as the choice of anaesthesia is usually based on clinical factors already present like amount of blood loss at the time of decision, placental localisation and whether or not the delivery is an emergency. Our findings are similar with the findings of Frederiksen et al [10] and Afolabi et al [14] who reported that general anaesthesia increased intraoperative blood loss and the need for blood transfusion as compared to regional anaesthesia. This difference can be caused by muscle relaxation and opening of the blood vessels with general anaesthesia.…”
Section: Discussionsupporting
confidence: 93%
“…However, we did not include this factor in our prediction model, as the choice of anaesthesia is usually based on clinical factors already present like amount of blood loss at the time of decision, placental localisation and whether or not the delivery is an emergency. Our findings are similar with the findings of Frederiksen et al [10] and Afolabi et al [14] who reported that general anaesthesia increased intraoperative blood loss and the need for blood transfusion as compared to regional anaesthesia. This difference can be caused by muscle relaxation and opening of the blood vessels with general anaesthesia.…”
Section: Discussionsupporting
confidence: 93%
“…DiVerent techniques were studied including regional analgesia and incisional-site analgesia [16][17][18]. Although CS is the most common gynecologic surgery preformed, previous studies regarding the advantages and disadvantages of the diVerent methods of anesthesia in CS deal primarily with maternal and neonatal complications [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of spinal anesthesia are potential hypotension, intrapartum nausea and vomiting, possibility of headaches in cases complicated by dural puncture and limited duration of action [9]. The advantages of general anesthesia are a faster induction, good ventilation, the ability to gain cardiovascular stability and lower rates of hypotension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations